The expert’s cadence, the novice’s rush: A multi-level analysis of cognitive rhythm in translation production under pressure - Yu Weng (PLoS ONE, 2026)
This study examines how time pressure and translator experience interact to shape the cognitive rhythm of translation production. Sixty-five Chinese-English translators’ (35 novices, 30 experienced) keystroke activities were tracked as they translated comparable texts under three time conditions: Short, Standard, and Free. Multi-level analyses captured micro-level behaviors (pausing, segmentation) and macro-level process organization (phase allocation, revision strategies). Results reveal experience-dependent adaptation. Both groups demonstrated increased fluency and production stability when time pressure was relieved, producing longer and more consistent text segments and engaging in more immediate self-correction. However, the two groups diverged fundamentally in their strategic responses. Experienced translators maintained stable production rhythms across all conditions and strategically allocated time to orientation and end revision, cleanly separating drafting from revision. Novices, in contrast, exhibited a reactive, blended strategy: drafting and revision were tightly coupled, and process efficiency depended heavily on external time constraints. Notably, novices’ behavioral pattern most closely resembled that of experienced translators under the moderate deadline, but they failed to capitalize on unlimited time for further strategic improvement. These findings suggest that translation expertise is characterized by metacognitive control over cognitive rhythm and resilience against external constraints. Novices, lacking such adaptive regulations, are prone to a cognitively costly, reactive process. The study’s implications extend beyond translation, highlighting the universal importance of strategic process management in professional practice and demonstrating how time constraints can serve as a pedagogical scaffold to help beginners develop adaptive expertise.